Emerging roles of noncoding micro RNAs and circular RNAs in bovine mastitis: Regulation, breeding, diagnosis, and therapy - Zong, Weicheng; Zhang, Tianying; Chen, Bing; Lu, Qinyue; Cao, Xiang; Wang, Kun; Yang, Zhangping; Chen, Zhi; Yang, Yi (Frontiers in Microbiology, 2022)
Bovine mastitis is one of the most troublesome and costly problems in the modern dairy industry, which is not only difficult to monitor, but can also cause economic losses while having significant implications on public health. However, efficacious preventative methods and therapy are still lacking. Moreover, new drugs and therapeutic targets are in increasing demand due to antibiotic restrictions. In recent years, noncoding RNAs have gained popularity as a topic in pathological and genetic studies. Meanwhile, there is growing evidence that they play a role in regulating various biological processes and developing novel treatment platforms. In light of this, this review focuses on two types of noncoding RNAs, micro RNAs and circular RNAs, and summarizes their characterizations, relationships, potential applications as selection markers, diagnostic or treatment targets and potential applications in RNA-based therapy, in order to shed new light on further research.